2020
DOI: 10.21203/rs.3.rs-38902/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence, predictors, and mortality of bloodstream infections due to methicillin-resistant Staphylococcus aureus in patients with malignancy: systemic review and meta-analysis

Abstract: Background: Cancer patients are more likely to develop and die of bloodstream infection (BSI) than noncancer patients. Methicillin-resistant Staphylococcus aureus (MRSA), which is associated with immense mortality and economic burden worldwide, is not covered by the recommended initial antibiotic therapy for cancer patients with BSI. This systemic review was performed to estimate the global methicillin-resistant Staphylococcus aureus (MRSA) prevalence among bacteremia in patients with malignancy, and further s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…Nearly 80% of catheter-related infections are caused by gram-positive organisms [2]. Staphylococci, streptococci, and enterococci carry the greatest burden of disease [22]. Staphylococcus aureus (S. aureus) infections are generally classified as being caused by methicillin-resistant S. aureus (MRSA) or methicillin-susceptible S. aureus (MSSA).…”
Section: Gram-positive Bacteriamentioning
confidence: 99%
See 2 more Smart Citations
“…Nearly 80% of catheter-related infections are caused by gram-positive organisms [2]. Staphylococci, streptococci, and enterococci carry the greatest burden of disease [22]. Staphylococcus aureus (S. aureus) infections are generally classified as being caused by methicillin-resistant S. aureus (MRSA) or methicillin-susceptible S. aureus (MSSA).…”
Section: Gram-positive Bacteriamentioning
confidence: 99%
“…Staphylococcus aureus (S. aureus) infections are generally classified as being caused by methicillin-resistant S. aureus (MRSA) or methicillin-susceptible S. aureus (MSSA). While the prevalence of MRSA bloodstream infections is relatively low, the proportion of surgical site infections caused by MRSA has substantially increased over the past 15 years and is associated with alarming mortality rates in neutropenic, adult cancer patients [2,22]. It has also been demonstrated that both MSSA and MRSA infections in non-neutropenic, cancer patients are serious clinical conditions frequently associated with the placement of a central venous catheter or an indwelling urinary catheter [14].…”
Section: Gram-positive Bacteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to the escalating incidences of ‘difficult to treat’ MDR pathogens, the use of conventional antibiotics has proven to be ineffective (Chadha et al, 2021c). According to published reports, this notorious pathogen has been correlated with high mortality rates of 15%–60% (Li et al, 2021). The endless race between the discovery of newer drugs and the development of antibiotic resistance is inclined towards the latter end (Chadha et al, 2021a).…”
Section: Introductionmentioning
confidence: 99%
“…2017; Li et al . 2021). MRSA is included on the ESKAPE pathogens, a group of bacterial species that due to increased acquisition of antimicrobial resistance have been increasingly difficult to treat, with increasing burden of disease and increased death rates due to treatment failure (Oliveira et al .…”
Section: Introductionmentioning
confidence: 99%